Bange for sin egen skygge? Om at undersøge selvbevidste organisationer - Grøn, Caroline Howard (Politik, 2012)
Through the formulation of 6 lessons, the article examines the challenges which a researcher faces when studying self-conscious organizations. Private and public organizations alike have to be concerned about their image and about the potential reputational damage if a researcher is let in and ends up making a criti- cal analysis of the organization. is concern can make the researcher’s life di cult and demands planning and a certain amount of awareness once the data collection has started. e article aims at preparing and improving this process.